Antiproton stopping power data for radiation therapy simulations. Issue 12 (December 2016) - Bailey, J.J.; Kadyrov, A.S.; Abdurakhmanov, I.B.; Fursa, D.V.; Bray, I.
Highlights: A convergent close-coupling method is used for the calculation of stopping powers. Tabulated results for antiproton stopping in H, He, H2, and H2 O are presented. The total stopping power is separated into its individual contributions. Abstract: Stopping powers of H, He, H2, and H2 O targets for antiprotons have been calculated using a convergent close-coupling method. For He and H2 targets electron–electron correlations are fully accounted for using a multiconfiguration approximation. Two-electron processes are included using an independent-event model. The water molecule is described using a neon-like structure model with a pseudo-spherical potential. Results are tabulated for the purpose of Monte Carlo simulations to model antiproton transport through matter for radiation therapy.